Negotiating boundaries: Framing and sense-making in a design thinking project with an elderly community - Minné, D.; Conrad, N.; Douglas, T. S.; Mutsvangwa, T. (South African Journal of Higher Education, 2023)
In recent years Design Thinking has established itself as a popular methodology for unlocking the creative potential that drives innovation, and scholars have begun to apply it in the health sector. However, as a conceptual framework, the approach has been criticised for lacking coherence and empirical validation. Although few have explicitly highlighted the central role of frame management in Design Thinking, we propose that much of the innovative potential, as outlined in its founding principles, stems from a concern with mental processes that contextualise new information to give it meaning and significance. Here we sought to address this gap by studying the framing process in two design teams tasked with developing solutions to assist an elderly population with compliance with medication schedules. Findings from a qualitative analysis indicate that although Design Thinking has clear merit as a methodology for helping designers shift beyond their immediate field of expertise, feedback and observations gathered during engagement with stakeholders inevitably appear to make their way through a filtering process where specific interpretations and meanings become censored and constrained by dominant discourses. Especially in the health sector, where information is sensitive, critical attention to the underlying value systems and prevailing discourses that influence designers’ implicit frames of reference is needed if Design Thinking is to gain credibility as a scientifically robust method for innovation. design thinking, framing, health innovation, medication adherence